Conversion From Intrathecal Morphine to Oral Methadone. Issue 3 (1st May 2002) - Gebhardt, Rodolfo; Kinney, Michelle A.O.
Abstract : Background and Objectives: Methadone is an inexpensive and highly effective analgesic when titrated appropriately. Its equianalgesic ratio with other opioids is variable, however. We present a case of conversion from high-dose intrathecal (IT) morphine to oral methadone. Case Report: A 37-year-old man was admitted to the orthopedic service due to increased lower back pain. He had a history of recurrent L5 plasmacytoma, an L5 corpectomy, and L3-S1 fusion with instrumentation. An implanted neuraxial drug delivery device had been placed at another institution for back pain. Evaluation suggested infection involving the hardware. The patient underwent hardware removal, debridement of osteomyelitis, and removal of the IT catheter. The patient's analgesia was converted from IT to intravenous morphine and then to oral methadone. Conclusions: The conversion from high-dose IT morphine to oral methadone has not been previously described. The case presents higher IT morphine to oral methadone conversion ratio than might be expected based upon conventionally used equianalgesic tables.